Upaya Satuan Pendidikan dalam Mencegah Perundungan Peserta Didik: Tinjauan Studi Literatur: - Anggraini, Liza; Suryadi, Suryadi; Masbirorotni, Masbirorotni (LPPM Institut Pendidikan Nusantara Global, 2024)
The Education Unit is a place where educated and knowledgeable future generations of the nation are created, because there is a learning process from educators to mature children into people of high character, not only at school but can be applied in everyday life. However, the purpose of this educational unit sometimes does not meet expectations, there are still cases of problems that come from schools due to a lack of absorption of the values and norms taught by educators. The research study was carried out by means of a literature study with a narrative literature review approach. Based on the researcher's analysis, there are several efforts that can be made in schools, namely 1) a teacher approach by providing education and advice that can shape an educated personality so as to avoid bullying, 2) asking for help from other fellow teachers when it cannot be done personally, 3) installing anti-bullying posters in every corner of the school as a form of socialization, 4) assistance from Babinkamtibmas in providing education on the impact of bullying, and 5) assistance from social services in the form of rehabilitation activities for children who are deemed to experience social barriers in socializing.